Hederlighet, drogfrihet, kamratskap och solidaritet - Kim Silow Kallenberg (Kulturella Perspektiv, 2023)
In this article the life stories of ex-convicts are analysed. The aim is to analyse class and masculinity in the narratives of ex-convicts, by investigating how they construct respectability. The four men that have been interviewed are all active in crime preventive and rehabilitating organisations. The interviews have been analysed from a class and masculinity perspective, using Beverley Skeggs concept of respectability as the main analytical concept. The analysis shows that the life stories of the interviewees are often constructed as chronological narratives, where destructive life paths are explained through childhood problems and trauma. Will power and hard work are understood as important factors for turning your life around. Factors that are often associated with what is understood as traditional male traits. The analysis further shows that male homosociality and identification is understood as important tools to change life-style.